Molecular engineering of non-fullerene acceptors based on thiophene-fused end groups for fullerene-free organic solar cells. (February 2022) - Jeong, Soyeong; Je, Hwanil; Lee, Ji Hyun; Lee, Seung Hun; Jang, Soo-Young; Park, Kiyoung; Kang, Hongkyu; Kwon, Soon-Ki; Kim, Yun-Hi; Lee, Kwanghee
Abstract: A new series of ITIC-based non-fullerene acceptors (NFAs), namely m-ITTC-Oeh-SM (IT-SM) and m-ITTC-Oeh-DSM (IT-DSM), which contain thiophene-substituted end groups (EGs) with single and double thiomethyl side chains, respectively, were designed, synthesized, and characterized in this study. The IT-SM NFA exhibited a narrower optical band gap, redshifted absorption, stronger crystallinity, and smoother surface morphology than those of the IT-DSM NFA. Organic solar cells (OSCs) based on the polymer donor PBDB-T and IT-SM reported a power conversion efficiency (PCE) of 8.98% with the addition of 0.5 v/v% 1, 8-diiodooctane (DIO), whereas the PCE of the PBDB-T:IT-DSM device was equal to 3.02%. The difference between the PCE values of these two devices was attributed to the gap of the short-circuit current and fill factor. Detailed analyses of the charge transport, collection, and morphology of the blend films were performed to investigate the difference between the device performances. The results of this study can help formulate detailed guidelines for the commercialized production of NFAs. Highlights: Novel ITIC-based nonfullerene acceptors with thiophene end groups were synthesized. Thiomethyl side chains of end group influence the photovoltaic performance. Synthesized nonfullerene acceptors show PCE of 3.0–9.0% in photovoltaic devices. The number of side chain strongly influence the morphologies of photoactive layers.